Inductive Bible study : observation, interpretation, and application through the lenses of history, literature, and theology - Fuhr, Richard Alan, Jr., 1971-; Köstenberger, Andreas J., 1957- (B & H Academic, 2016)
"Inductive Bible study is a practical, relevant, and time-tested approach to interpreting Scripture. This volume incorporates insights from contemporary evangelical hermeneutics into an approachable, step-by-step process moving from observation through interpretation and on to the application of God's Word. Each step is viewed through the lenses of the hermeneutical triad, exploring the historical, literary, and theological elements that impact how one observes, interprets, and applies the Bible. Chapter by chapter, Inductive Bible Study explores a broad representation of biblical texts as it illustrates the steps of inductive methodology across the literary landscape of Scripture."--Back cover